Estrategia lúdica para fortalecer la motricidad fina en los estudiantes de segundo grado de egb de la unidad educativa “Santo Domingo de los Colorados”. - Argudo Ibarra, Karen Lisbeth (2025)
The incorporation of playful activities in the educational environment has become a strategic tool for introducing children to meaningful learning experiences in pleasant settings and in a natural way, fostering skill development. The objective of this research is to develop a playful strategy to strengthen fine motor skills in 2nd-grade Basic General Education (BGE) students at the "Santo Domingo de Los Colorados" Educational Unit. Due to the COVID-19 pandemic, weaknesses emerged in academic activities requiring precise movements, such as cutting, coloring, modeling, and gluing—fundamental skills for the later writing process. This research is based on previous studies and scientific articles on playful strategies and fine psychomotricity in children, implemented a qualitative-quantitative approach. It was a bibliographic and field study of a descriptive nature, involving a population of 166 people. The results indicated that the implementation of a playful strategy will strengthen motor development and, consequently, consolidate the writing process. Additionally, it was observed that this strategy would encourage interaction both inside and outside the classroom, involving parents in various activities. In conclusion, the study demonstrated that the use of playful strategies provides significant benefits for children's fine motor skills by offering fun experiences and fostering creative expression, thereby improving their hand-eye coordination, precision, and proper object handling.